An Evaluation of the Significance of the Accuracy of a Starting Model in Computer-Aided Vertical Electrical Sounding (Yes) Interpretation - Bayowa, Oyelowo Gabriel (2015)
The aim of this research was to evaluate the degrees of accuracy of the starting model parameters of the conventional partial curve matching, the asymptote/inflection points and the type curve controlled guess techniques of Vertical Electrical Sounding (VES) preliminary interpretation. The study involved both model studies and field data tests.